Monotonic and cyclic shear behaviors of incineration bottom ash under constant volume condition - Zhang, Zhibo (2023)
Incineration is becoming a popular treatment method of waste in the last several decades which makes the study of the mechanical properties of incineration ash more important. This study uses a cyclic simple shear device to test the monotonic and cyclic shear behavior of a type of incinerated bottom ash (IBA) produced in Singapore. It's found that the friction angle of IBA is 32 degrees with zero cohesion, and no clear peak strength is observed at a medium-dense condition. As shear strain increases, the shear stress normalized by current vertical stress is independent of consolidation vertical stress. Contract behavior shows first followed by continuous dilation. The cyclic shear ratio (CSR) under 100 kPa vertical stress has an almost logarithmic linear correlation with the number of cycles. The slope of shear stress-shear strain (τ-γ) curve under the cyclic shear condition also follows the ultimate state line determined from monotonic shear. During all the cyclic shear tests, IBA fails by reaching maximum double amplitude shear strain (7.5%) while pressure ratio equivalent to 1.0 cannot be reached.